Reconstruction of Upper Limb Long Bone Defects with Vascularized Free Fibula in Pediatric Population: A Review of the Functional Outcomes - Goher, Maimoona; Rashid, Mamoon; Ur Rehman, Saad; Shabbir, Farwa; Aslam, Shahzaib; Kifayat, Amna (Pakistan Armed Forces Medical Journal, 2024)
Objective: The aim of our study was to evaluate the functional outcomes in paediatric patients who underwent upper limb long bone reconstruction with vascularised free fibula. Study Design: Retrospective descriptive study. Place and Duration of study: Department of Plastic Surgery, Shifa international Hospital, Islamabad Pakistan from Jun 2015 to Jul 2020. Methodology: All paediatric patients who underwent upper limb long bone defect reconstruction secondary to sarcoma resection were included in the study. Radiological and functional assessment was done pre and post operatively. Outcomes were assessed in terms of surgical wound dehiscence, flap loss, donor site morbidities and functional outcomes. Functional outcomes were evaluated using Musculoskeletal Tumor Scores for upper limb and pediatric Toronto Extremity Salvage Score for upper limb. Results: Total of 14 paediatric patients were operated during 5-year period of June 2015-July 2020. Age of the patients ranges from 9 - 15(12.5) years. All the limbs were successfully salvaged with no flap loss and no significant donor site morbidity. Functional latissimus dorsi flap was done in 6 patients to achieve elbow flexion. Overall musculoskeletal tumor society Score was 82% and pediatric toronto exteremity salvage score mean was 82.43%. Conclusion: Vascularised free fibula is a reliable and cost-effective option for bridging bone gaps in paediatric patients after sarcoma resection with optimal functional outcomes.